2020
DOI: 10.1186/s12889-020-08578-9
|View full text |Cite
|
Sign up to set email alerts
|

Social judgments on abortion and contraceptive use: a mixed methods study among secondary school teachers and student peer-counsellors in western Kenya

Abstract: Background: In Kenya, unsafe abortion is the leading cause of maternal deaths in adolescent girls aged 15-19 years, and a majority did not use a modern contraceptive before becoming pregnant. The aim of this study was to explore attitudes related to abortion and contraceptive use among secondary school teachers and student peercounsellors in a low-resource setting in western Kenya. Methods: A mixed methods design, combining a questionnaire-survey and focus group discussions (FGDs), was utilised to explore atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 29 publications
2
25
0
1
Order By: Relevance
“…Our observations regarding unsafe abortions, combined with the frequent discussion of suicide, speaks to the desperation adolescent girls feel and the lengths they are willing to go to avoid carrying a pregnancy to term (Håkansson et al. 2020; Jayaweera et al. 2018; Levandowski et al.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Our observations regarding unsafe abortions, combined with the frequent discussion of suicide, speaks to the desperation adolescent girls feel and the lengths they are willing to go to avoid carrying a pregnancy to term (Håkansson et al. 2020; Jayaweera et al. 2018; Levandowski et al.…”
Section: Discussionmentioning
confidence: 91%
“…This barrier can be reduced by including contraceptive counseling in routine health care for adolescents living with HIV, scheduling adolescent‐only clinic days, or building stand‐alone clinics with staff trained to provide a range of adolescent‐appropriate services (Håkansson et al. 2020; Hagey et al. 2015; Mugwanya et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies confirm that most of the adolescents faced morbidity and mortality from unsafe abortion due to their low contraceptive knowledge and uptake. 13 Many of the respondents identified side effects of using contraceptives, especially related to menstruation. It was found that the most common side effects among the participants included irregular patterns of menstruation, excessive bleeding, and sometimes discontinuation of the menses.…”
Section: Discussionmentioning
confidence: 99%